Household pork consumption behaviour in Vietnam: Implications for pro-smallholder pig value chain upgrading - Nga Nguyen Thi Duong; Nguyen Thi Thu Huyen; Pham Van Hung; Duong Nam Ha; Tran Van Long; Dang Thi Be; Unger, Fred; Lapar, Ma. Lucila (Vietnam National University of Agriculture, 2015)
Pork represents more than 70% of meat consumption in Vietnam, and pig production provides livelihood for more than 4 million small farmers in the country. Understanding pork consumption behaviour is thus important for upgrading the pig value chains in Vietnam. The study is conducted with 416 households in Hung Yen and Nghe An provinces. The results confirm that pork is the most widely eaten animal source food in Vietnam (about 24.7 kg per capita and year), consumed by more than 95% of the population of different ages and gender. A household spends about USD 30 monthly for pork, accounting for 13% of total food expenditure. Meanwhile, other types of meat appear to be weak substitutes to pork. While consumers select market outlets for pork based on cleanliness, trust in sources, and the absence of disease in pork sold, 99% of them still buy meat in traditional, wet markets. This, coupled with the fact that meat quality is not traceable in the value chain and only 3% of respondents trust in their regular meat supply, implies that the pig value chain, especially the formal/ modern retailing sector in Vietnam, has not yet gained consumer trust. Given saturated pork demand with more than 95% of respondents planning to sustain or decrease their pork consumption, it’s unlikely that pork consumption behaviour will significantly change for the majority of Vietnamese consumers. Several potential implications are drawn for upgrading the pig value chains: (i) Organizing small farms into groups applying good practices that allow meat to be traceable and certified by trusted institutions; (ii) Developing a quality assurance system that can be feasibly established under smallholder conditions, and complies with minimum quality and safety standards tailored to Vietnam’s context, (iii) Strengthening capacity to collect appropriate market information to provide pig producers, particularly smallholders, reliable meat demand and supply forecast to better serve their target consumers; and (iv) Improving cost and quality competitiveness in pig value chains. These are important considerations especially when Vietnam becomes deeply integrated into the global and regional markets when the Trans-Pacific Strategic Economic Partnership Agreement is officially put into practice.